Deregulated FOX genes in Hodgkin lymphoma. Issue 11 (17th July 2014) - Nagel, Stefan; Meyer, Corinna; Kaufmann, Maren; Drexler, Hans G.; MacLeod, Roderick A. F.
<x xml:space="preserve">Abstract</x> FOX genes encode transcription factors which regulate basic developmental processes during embryogenesis and in the adult. Several FOX genes show deregulated expression in particular malignancies, representing oncogenes or tumor suppressors. Here, we screened six Hodgkin lymphoma (HL) cell lines for FOX gene activity by comparative microarray profiling, revealing overexpression of FOXC1 and FOXD1, and reduced transcription of FOXN3, FOXO1, and FOXP1. In silico expression analyses of these FOX gene candidates in HL patient samples supported the cell line data. Chromosomal analyses demonstrated an amplification of the FOXC1 locus at 6p25 and a gain of the FOXR2 locus at Xp11, indicting genomic aberrations for their upregulation. Comparative expression profiling and ensuing stimulation experiments revealed implementation of the TGFβ‐ and WNT‐signaling pathways in deregulation of FOXD1 and FOXN3. Functional analysis of FOXP1 implicated miR9 and miR34a as upstream regulators and PAX5, TCF3, and RAG2 as downstream targets. A similar exercise for FOXC1 revealed repression of MSX1 and activation of IPO7, both mediating inhibition of the B‐cell specific homeobox gene ZHX2. Taken together, our data show that aberrantly expressed FOX genes and their downstream targets are involved in the pathogenesis of HL via deregulation of B‐cell differentiation and may represent useful diagnostic markers and/or therapeutic targets. © 2014 Wiley Periodicals, Inc.